Osvrt na knjigu The Height of Prophet Adam: At the Crossroads of Science & Scripture Muntasira Zamana (Context: Journal of Interdisciplinary Studies, 2023)
Osvrt na knjigu The Height of Prophet Adam: At the Crossroads of Science & Scripture Muntasira Zamana